2020
DOI: 10.1038/s41598-020-78511-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-set enrichment analysis facilitates functional interpretation of microbiome profiling data

Abstract: The commensal microbiome is known to influence a variety of host phenotypes. Microbiome profiling followed by differential abundance analysis has been established as an effective approach to study the mechanisms of host-microbiome interactions. However, it is challenging to interpret the collective functions of the resultant microbe-sets due to the lack of well-organized functional characterization of commensal microbiome. We developed microbe-set enrichment analysis (MSEA) to enable the functional interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…For example, the sphingolipid metabolism pathway was enriched in LTS samples, which might be attributed to Sphingomonas and Enterococcus ; protein processing in the endoplasmic reticulum, which belongs to the genetic information processing pathway, might be attributed to Sphingomonas and Megasphaera ( Figure 3 ). Microbiome set enrichment analysis ( 33 ) was also performed to explore the relationship between differential genera and human diseases. Our results showed that most of the differential genera were involved in tumor immunity pathways, such as IL-17 and TNF signaling ( 34 , 35 ) ( Supplementary Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the sphingolipid metabolism pathway was enriched in LTS samples, which might be attributed to Sphingomonas and Enterococcus ; protein processing in the endoplasmic reticulum, which belongs to the genetic information processing pathway, might be attributed to Sphingomonas and Megasphaera ( Figure 3 ). Microbiome set enrichment analysis ( 33 ) was also performed to explore the relationship between differential genera and human diseases. Our results showed that most of the differential genera were involved in tumor immunity pathways, such as IL-17 and TNF signaling ( 34 , 35 ) ( Supplementary Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…To explore potential associations between differentially abundant microbial genera and the host transcriptome, we performed microbe-set enrichment analysis (MSEA) 24 , whereby the differentially abundant microbes we identified were tested for enrichment against a library of ~1,300 gene-labeled microbe-sets, and the significant microbe-gene associations were visualized in Figure 4 and tabulated in Supplementary Table 5. The union set of genes labeling significantly enriched microbe-sets was in turn tested for enrichment against the Hallmark compendium using hypeR (Supplementary Table 6) The significant genesets overlapping with those found in the host analysis in Figure 2A are also displayed in Figure 4 (center).…”
Section: Differentially Abundant Microbes In Pmls and Oscc Are Associ...mentioning
confidence: 99%
“…The properties shared by these clades are often not obvious, but could include common environmental exposures, metabolic or ecological requirements, or physiological characteristics. Although nascent attempts to apply concepts of GSEA to results of microbiome differential abundance analysis exist [15][16][17][18] , major obstacles have prevented their broad utility and adoption. The most significant obstacle has been the lack of comprehensive databases of signatures designed for enrichment analysis, such as those available for GSEA including GO 19 , KEGG 20 , MSigDB 21,22 , and GeneSigDB 23 .…”
Section: Introductionmentioning
confidence: 99%